Penerapan Expressive Writing pada Tn. G dan Tn. Y dengan Masalah Keperawatan Harga Diri Rendah Kronis di Ruang Petruk Gareng RSJD Provinsi Jambi - Putra, Dimas Hendri; Yuliana, Yuliana (Universitas Batanghari Jambi, 2024)
Low self-esteem is a feeling of worthlessness, insignificance, and low self-esteem resulting from negative self-evaluation so that it requires management to increase self-esteem. One non-medical method is expressive writing therapy which aims to forget the contents of deep thoughts and feelings thereby increasing self-esteem. This research uses a pre-test-post-test method through a process of interviews, observation and using stationery. The subject of this research is the nursing problem of chronic low self-esteem with an intervention time of 6 days. The results of the research show that there is an effect of providing expressive writing therapy. Observation results showed a decrease in symptoms in patients with chronic low self-esteem and increased feelings of worth and self-confidence